PG92 The use of virtual simulation during a pandemic. (10th November 2020) - Kelly, Louise; Powell, Natalie; Cooper, Andrea; Roge, Hannah; Hodgson, Aimee; Zafurallah, Intikhab
Abstract : Introduction: In-situ simulation training requires participants to be in close proximity and has been suspended due to COVID-19 transmission risk. KIDSNTS conducts regular multidisciplinary training courses, which includes in-situ simulation. Due to the current pandemic, the simulation faculty has adapted their training to include virtual simulation sessions. To study whether virtual simulation sessions is an effective modality for multi specialty health care workers (HCWs) training. Methods: Thirty (30) candidates were selected to attend a virtual course which included three hours of simulation and debriefing. Candidates were pre assigned into 3 groups, based on their specialty and job role. Each group watched a 10 minutes pre-recorded simulation episode with two facilitators via Zoom. Using the advocacy inquiry (AI) model, each group spent 50 minutes debriefing. Candidates were asked to complete an anonymous questionnaire (utilising likert scale) following the simulation sessions. Results: Twenty-seven (90%) of the selected candidates attended the course (table 1 ) of which 96% (figure 1 ) completed a questionnaire. 100% of the candidates achieved their learning objectives and would recommend the course. 72% and 96% respectively score the simulation session as excellent (figure 2 +3). Discussion and Conclusion: Virtual simulation and debriefing appears to be a positive adjunct to multi-specialty HCWs training. This provides a quality learning experience facilitating multidisciplinary discussions and shared learning. Setting clear learning objectives and zoom rules enabled good engagement. There will be limitations where hands on practical skills are required. For non-technical skills virtual simulation has a definite role in training. Further research is indicated to inform the validity of virtual simulation in training.